Extra life : a short history of living longer - Johnson, Steven, 1968- (Riverhead Books, 2021)
"As a species, humans have doubled their life expectancy in one hundred years. Medical breakthroughs, public health institutions, rising standards of living, and the other advances of modern life have given each person about 20,000 extra days on average. This book attempts to help the reader understand where that progress came from and what forces keep people alive longer. The author also considers how to avoid decreases in life expectancy as public health systems face unprecedented challenges, and what current technologies or interventions could reduce the impact of future crises. This work illuminates the power of common goals and public resources; the work of activists struggling for reform, and of scientists sharing their findings open-source-style; and of non-profit agencies spreading innovations around the world"--